Mediasi Literasi Keuangan Dalam Memprediksi Risk Tolerance Pada Anggota Organisasi Muhammadiyah Di Jawa Timur - Nurullaili Mauliddah; Muhammad Alhakim Danurwindo; Bahrul Ulum; Octavia Ika Wibowo; Galuh Nichayah Pravitasari (SENTRALISASI, 2023)
This study aims to predict risk tolerance and determine the role of financial literacy in members of the Muhammadiyah Organization in East Java through the mediation of financial literacy. This study took a sample of 107 respondents by using SEM-PLS analysis. The study results show that financial attitude, financial behaviour and income cannot predict risk tolerance. However, the effect of these independent variables on risk tolerance can be strengthened through the mediation of financial literacy. Thus, this study implies that members of the Muhammadiyah organization in East Java have a good level of risk tolerance supported by a good knowledge of financial concepts based on the measuring instrument in this research variable.